2018
DOI: 10.1073/pnas.1721469115
|View full text |Cite
|
Sign up to set email alerts
|

Complete biosynthesis of noscapine and halogenated alkaloids in yeast

Abstract: Microbial biosynthesis of plant natural products from simple building blocks is a promising approach toward scalable production and modification of high-value compounds. The pathway for biosynthesis of noscapine, a potential anticancer compound, from canadine was recently elucidated as a 10-gene cluster from opium poppy. Here we demonstrate the de novo production of noscapine in , through the reconstruction of a biosynthetic pathway comprising over 30 enzymes from plants, bacteria, mammals, and yeast itself, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
239
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(248 citation statements)
references
References 41 publications
6
239
2
1
Order By: Relevance
“…For simplicity, we will refer to this truncated Coptis japonica homologue as tNCS. Previous studies have also reported improved titers upon truncation of NCS enzymes, with evidence suggesting that this effect is due to improved expression and/or stability of the protein [47][48][49] . (S)-Norcoclaurine titer was directly dependent on the expression level of tNCS, with stronger promoters and copy numbers resulting in higher (S)-norcoclaurine titers ( Fig.…”
Section: Expression Of Most Active Ncs Variant Causes Cytotoxicity Inmentioning
confidence: 95%
“…For simplicity, we will refer to this truncated Coptis japonica homologue as tNCS. Previous studies have also reported improved titers upon truncation of NCS enzymes, with evidence suggesting that this effect is due to improved expression and/or stability of the protein [47][48][49] . (S)-Norcoclaurine titer was directly dependent on the expression level of tNCS, with stronger promoters and copy numbers resulting in higher (S)-norcoclaurine titers ( Fig.…”
Section: Expression Of Most Active Ncs Variant Causes Cytotoxicity Inmentioning
confidence: 95%
“…The race to develop high‐yield, ethanol‐producing yeast strains for the biofuel industry is led by large companies such as Lallemand, DuPont, and Novozymes. Pioneering work has successfully engineered S. cerevisiae to produce plant‐derived therapeutics including the antimalarial drug artemisinin (Paddon et al, ); the cancer therapeutics taxol, noscapine, and taxediene (Ding et al, ; Li et al, ); and endocannabanoid and opioid analgesics (Galanie et al, ; Luo et al, ; Zirpel, Degenhardt, Martin, Kayser, & Stehle, ). Cao et al () designed a P. pastoris platform to produce multiple biologics in a single strain or in co‐cultures of two strains, and as a proof of principle, they produced and isolated three protein biologics.…”
Section: Yeasts Have a Large And Growing Role In The Emerging Bioeconomymentioning
confidence: 99%
“…Interestingly,i np arallel with this work, the synthesis of noscapine and halogenated BIAs in yeast has been reported using ar eported TyrH and DODC,t ogether with other downstream biosynthetic enzymes in vivo. [43] While some halogenated BIAs were detected, it was unclear how much was produced or what the stereoselectivity was.H ere,t he one-pot in vitro cascades demonstrate an extremely powerful strategy for introducing molecular diversity using sustainable catalysts.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[43] While some halogenated BIAs were detected, it was unclear how much was produced or what the stereoselectivity was.H ere,t he one-pot in vitro cascades demonstrate an extremely powerful strategy for introducing molecular diversity using sustainable catalysts. Thef irst was at wo-step reaction using EfTy rDC to convert 8 into 14,which was then reacted with 19, yielding (S)-23 in 25 %y ield of isolated product (82 %y ield by HPLC) and greater than 97 % ee.…”
mentioning
confidence: 99%